Pengembangan Sistem Informasi Konsultasi Dokter Menggunakan Framework Laravel - Muhammad Mirza Ramdoni; Muhammad Izman Herdiansyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The purpose of the research conducted was to examine the development of a web-based doctor consultation system in dr. Angga Dwi Pratomo and dr. Novaria Yuasa and provide easy medical consultations to patients. The place of practice which is still not optimal because it still uses the manual method in medical consultations. The method used for the development of this consulting information system uses the waterfall model on the grounds that this model is coherent. The benefits of research can carry out the consulting process quickly and efficiently. This application uses the Laravel framework which can make it easier for writers to make applications. The result of this built application is a web-based consulting information system that can provide patient convenience in consulting, patient data storage and information services that are easier and faster. The application that was built was made using tools such as sublime, MySQL, XAMPP as a database with HTML and PHP programming languages coupled with the Laravel Framework for developing software systems referring to the waterfall model which is one of the software development models, where the progress of a process is seen as continuous. flowing down like a waterfall. In the Waterfall Model, each stage must be sequential, and you cannot jump to the next stage, you must complete the first stage and then proceed to the second stage and so on. Which consists of several stages, namely reuirement or specification of system requirements, system design, system implementation, system trial, system operation, and system maintenance.